Targeted next-generation sequencing identifies molecular subgroups in squamous cell carcinoma of the head and neck with distinct outcome after concurrent chemoradiation - Tinhofer, Ingeborg; Stenzinger, Albrecht; Endris, Volker; Weichert, Wilko (Annals of oncology, 2016)
BackgroundBased on epidemiological (HPV status, smoking habits) and clinical risk factors (T/N stage), three subgroups of patients suffering from locally advanced oropharyngeal carcinoma with significantly different outcome after concurrent chemoradiation (cCRTX) can be distinguished. Mutational profiling by targeted next-generation sequencing (NGS) might further improve risk stratification.Patients and methodsPatients with stage IV squamous cell carcinoma of the oropharynx and hypopharynx who had been enrolled in a randomized phase III trial (ARO-0401) comparing two regimens of cCRTX and from whom archival tumor specimens were available were included. The HPV status was determined by p16 immunostaining and detection of HPV DNA. Targeted NGS covering 45 genes frequently altered in squamous cell carcinoma of the head and neck (SCCHN) was applied for detection of non-synonymous somatic and germline mutations. Interference of mutational profiles with cCRTX efficacy was determined.ResultsThe prognostic value of the ‘Ang’ risk model could be confirmed in the total biomarker study cohort (N = 175) as well as the patient subgroup for which mutational profiles could be established (N = 97). Mutations in genes involved in phosphoinositide 3-kinase (PI3K), receptor tyrosine kinase (RTK), and p53 signaling pathways were significantly enriched in the low- (N = 7), intermediate- (N = 20), and high-risk group (N = 70), respectively. Mutations in TP53 identified a subgroup of high-risk patients with dismal outcome after cCRTX. No prognostic relevance was observed for mutations in PI3K and RTK signaling pathways in the low- and intermediate-risk groups, respectively. Mutated NOTCH1 and two functional KDR germline variants (rs2305948, rs1870377) were associated with improved outcome in all risk groups. All genetic markers (TP53, NOTCH1, KDR) remained independent prognosticators of OS in the multivariate model.ConclusionA potential of targeted NGS for risk classification of SCCHN cases beyond HPV status and clinical factors was demonstrated.